Comparative effects of ultrasonic and conventional sealer placement techniques on endodontic sealer layer quality: a systematic review and meta-analysis of in vitro studies - Avishikta Banerjee; Niranjan Harikrishna; Aritro Bhattacharyya; Nishmitha Hegde; Mithra N. Hegde (Frontiers in Dental Medicine, 2026)
Aim This systematic review aims to critically appraise the existing literature on the influence of ultrasonic sealer placement techniques compared to other sealer placement methods on the quality of the sealer layer coated on root canal walls. The sealer layer quality was assessed based on the depth of sealer penetration into dentinal tubules, the extent of canal wall coverage with sealer, interfacial sealer adaptation, void formation, and push-out bond strength. Methodology A comprehensive literature search was conducted in PubMed, Scopus, and Web of Science, following the PRISMA guidelines, covering studies published between 2000 and 2026. In vitro studies comparing ultrasonic and non-ultrasonic sealer placement techniques, assessing the sealer layer quality, were included. 7,007 records were initially identified, of which 10 studies met the eligibility criteria. A standardised form was used for data extraction, and the risk of bias was assessed using the Quality Assessment Tool for in-vitro Studies (QUIN). A two-level random-effects meta-analysis (REML) was performed using the metafor package in R for sealer penetration depth and percentage of canal wall coverage outcomes. Results 10 in vitro studies were assessed in the systematic review, of which 6 were included in the meta-analysis. Meta-analysis of sealer penetration depth ( k = 17; 3 studies) yielded a pooled WMD of 254.66 µm (95% CI: 180.88–328.44; p < 0.001; I 2 = 100%) favouring ultrasonic activation. For the percentage of canal wall coverage ( k = 27; 4 studies), the pooled WMD was 17.79% (95% CI: 9.73–25.86; p < 0.001; I 2 = 99.1%), also favouring ultrasonic activation. Qualitative synthesis further indicated more favourable interfacial adaptation, reduced void formation, and higher push-out bond strength with ultrasonic sealer placement. Conclusions Within the limitations of laboratory evidence, ultrasonic methods of sealer placement were associated with improved sealer layer quality compared with other methods; however, given the substantial heterogeneity among included studies and the exclusively in vitro nature of the evidence, these findings should not be interpreted as indicating clinical superiority without further clinical validation. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/view/CRD420261303375 , identifier PROSPERO: CRD420261303375.